Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5505/agri.2014.25582
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Analgesic Efficacy of Gabapentin and Nimesulide in the Functional Endoscopic Sinus Surgery

Abstract: Summary Objectives: Preemptive analgesia is an important factor in controlling the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Figure and Table detail the 133 trials we included in the review, with our categorisation of risks of bias in Fig. . We excluded one duplicate trial , three trials that were unavailable as full text , five trials that did not use a placebo , one trial that used combination therapy and two uncontrolled trials .…”
Section: Resultsmentioning
confidence: 99%
“…Figure and Table detail the 133 trials we included in the review, with our categorisation of risks of bias in Fig. . We excluded one duplicate trial , three trials that were unavailable as full text , five trials that did not use a placebo , one trial that used combination therapy and two uncontrolled trials .…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12] For sinonasal procedures such as endoscopic sinus surgery (ESS) and septoplasty, prior RCTs have found that gabapentin administered preoperatively resulted in reduced pain levels and opioid consumption intraoperatively or immediately after surgery. [13][14][15][16][17] Most recently, a retrospective cohort study with 57 patients investigated the impact of preoperative gabapentin on postoperative pain control for 1 week after ESS and/or septoplasty. However, they did not find any analgesic or opioid cessation benefits to persist after the 7-day followup period.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] The use of precisely dosed modern intravenous anesthetic agents, together with proper patient positioning,[ 4 ] allows us to manage hemodynamic parameters during surgery and thus to easily control hemodynamics. [ 5 ] For achieving favorable operative conditions, many drugs such as remifentanil,[ 5 ] propofol, sevoflurane, desflurane,[ 6 ] desmopressin,[ 7 ] dexmedetomidine, clonidine,[ 8 ] and gabapentin[ 9 ] have already been used with varied success rate.…”
Section: Introductionmentioning
confidence: 99%